THE RELATIONSHIP BETWEEN BILINGUAL EDUCATION AND FUTURE EMPLOYMENT OPPORTUNITIES - Sultanova Shohistaxon Shavkatovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This article investigates the link between bilingual education and future employment prospects in an increasingly globalized economy. It examines how proficiency in multiple languages, gained through structured bilingual programs in early and primary education, can enhance an individual’s career opportunities, adaptability in the labor market, and earning potential. Drawing on international case studies and labor market data, the paper highlights the advantages of bilingualism for workforce competitiveness, cross-cultural communication, and access to global networks. It also considers challenges such as unequal access to quality bilingual programs and the need for policy measures to ensure equitable opportunities.